2014
DOI: 10.1007/s11897-014-0203-y
|View full text |Cite
|
Sign up to set email alerts
|

Educational Challenges to the Health Care Professional in Heart Failure Care

Abstract: The purpose of this review is to discuss the educational challenges faced by health care professionals in the care and management of patients with heart failure (HF). Self-care is a vital component in HF management, and promotion of self-care through education is a fundamental aspect of patient-centered care and supports patients' right to autonomy. The ultimate goal is not simply to convey knowledge, but to promote patients' understanding and to enhance their self-care skills by assuming an active role in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 91 publications
2
11
0
Order By: Relevance
“…This supports previous literature which indicated that patients with CHF expressed difficulty with translating knowledge into understanding how to engage in self-care activities and behaviors [50]. The incidental finding regarding a lack of awareness for their CHF diagnosis was supported by studies in which participants had minimal knowledge and were unaware they were diagnosed with CHF [37],[49]. Findings suggested the need for increased teaching when defining the disease process and differentiating it from other heart-related problems such as heart attack or arrhythmia.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This supports previous literature which indicated that patients with CHF expressed difficulty with translating knowledge into understanding how to engage in self-care activities and behaviors [50]. The incidental finding regarding a lack of awareness for their CHF diagnosis was supported by studies in which participants had minimal knowledge and were unaware they were diagnosed with CHF [37],[49]. Findings suggested the need for increased teaching when defining the disease process and differentiating it from other heart-related problems such as heart attack or arrhythmia.…”
Section: Discussionsupporting
confidence: 86%
“…These difficulties and barriers for performing self-care consist of misconceptions, lack of knowledge, age, race, ethnicity, socioeconomic status, and the limited amount of time for health care providers to deliver health education [36]. These factors were associated with increased readmission rates and poor outcomes in patient education and teaching [37][39]. Patient perceptions of instructions often differ which causes an inability of patients to fully understand the instructions provided by his or her doctor [40].…”
Section: Introductionmentioning
confidence: 99%
“…Like previous studies, we found disease awareness and self-management skills initially poor among Polish patients with HF. [31][32][33][34][35] However, "The Weak Heart" model, prepared based on HF guidelines and practical recommendations, 1,4,7,36 was effective in enhancing HF patients' knowledge and developing self-management behaviors. In the study, the education program was delivered by a certified nurse educator working in a given cardiology ward.…”
Section: Discussionmentioning
confidence: 99%
“…Poor understanding of their disease can lead to uncertainty, anxiety, fear and even disappointment for patients, including those with SSc-ILD [14,31]. Indeed, it has been shown that patients with SSc were fearful when their symptoms progressed but remained unexplained by HCPs [32].…”
Section: Discussionmentioning
confidence: 99%